AVALIAÇÕES DAS IMAGENS DE PESQUISA DE CORPO INTEIRO (PCI) OBTIDAS EM PACIENTES SUBMETIDOS AO TRATAMENTO DE RADIOIODOTERAPIA (PRÉ E PÓS-TRATAMENTO) (Brazilian Journal of Radiation Sciences, 2015)
Nuclear medicine is a medical specialty used for diagnosis and therapy of some diseases. For the treatment of differentiated thyroid carcinoma (papillary and follicular) Radioiodine therapy is employed, in order to eliminate the rest of thyroid tissue after removal of the thyroid (thyroidectomy). In Radioidoterapia is used radioisotope iodine-131 (¹ ³ ¹ I) as Sodium Iodide (NaI). The amount of the activity (dose) of ¹ ³ ¹ I administered is generally the responsibility of nuclear medicine, which is based on an image Research Length of the patient (pre-dose therapy PCI). PCI is also used after treatment (post-PCI therapeutic dose) to evaluate possible metastasis. The purpose of this study was to investigate the distribution of biokinetic ¹ ³ ¹ I at length and in some organs of the patient, in order to note any similiaridade. Exams PCI pre-dose and post-dose were analyzed, the anterior and posterior projections of ten patients. Contours in these images (ROI - Region Of Interest) were made in the whole body and in areas with high uptake of ¹ ³ ¹ I The total score was used in the calculation to obtain the percentage distribution of ¹ ³ ¹ I in the organs of the patient. The results showed that there similiaridade on the biodistribution of ¹ ³ ¹ I PCI between pre-dose and post-dose PCI. Therefore, it was found that it is valuable images of PCI pre-dose therapy as a way to assist the nuclear medicine physician in choosing the best activity to be administered to the patient in order to minimize the dose to adjacent organs.
Keywords: Thyroid Disease; Dosimetry; Nuclear Medicine.